2006
DOI: 10.1111/j.1365-313x.2006.02776.x
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in anti‐herbivore defense systems during neopolypoloidy – the functional consequences of instantaneous speciation

Abstract: SummaryAllopolyploid hybridization instantly merges two differentially adapted genomes into one individual. Allopolyploids are often evolutionarily successful, undergoing adaptive radiations despite the genetic and physiological challenges of merging genomes. We examine a suite of induced herbivore resistance traits in three independent lines of the synthetic allopolyploid Nicotiana · mierata (Nma) and its parent species, N. miersii (Nmi) and N. attenuata (Na), to determine how a complex polygenetic adaptation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 72 publications
10
22
0
Order By: Relevance
“…The breakdown of defensive systems in hybrids has received little attention from plant physiologists. However, metabolic screens of plant secondary compounds, which often play a defensive role against herbivore attack, have revealed unexpected patterns of inheritance in hybrid plants (Orians and Fritz 1995;Orians 2000;Pearse et al 2006;Yarnes et al 2008). In terms of hybrid outbreeding depression in animals, hybrids produced from parental species that are less related to one another are less Wt than hybrids produced from phylogenetically close relatives, as divergent evolutionary history is a good proxy for the divergence of physiological systems (Coyne and Orr 1989).…”
Section: Introductionmentioning
confidence: 98%
“…The breakdown of defensive systems in hybrids has received little attention from plant physiologists. However, metabolic screens of plant secondary compounds, which often play a defensive role against herbivore attack, have revealed unexpected patterns of inheritance in hybrid plants (Orians and Fritz 1995;Orians 2000;Pearse et al 2006;Yarnes et al 2008). In terms of hybrid outbreeding depression in animals, hybrids produced from parental species that are less related to one another are less Wt than hybrids produced from phylogenetically close relatives, as divergent evolutionary history is a good proxy for the divergence of physiological systems (Coyne and Orr 1989).…”
Section: Introductionmentioning
confidence: 98%
“…The last decade witnessed impressive advances in polyploidy research, with new results from Arabidopsis (Comai et al, 2000;Pontes et al, 2004), Brassica species (Lukens et al, 2006;Gaeta et al, 2007), cotton (Jiang et al, 1998), wheat (Han et al, 2003), and Nicotiana species (Lim et al, 2006;Pearse et al, 2006;Anssour et al, 2009). Most of these studies have focused on the genetic and genomic changes associated with the formation of polyploids, especially changes directly altering gene expression patterns, such as rapid and nonrandom changes including sequence elimination, changes in the DNA loci, and intergenomic cross talk, for example, transposon activation, chromosomal rearrangements, and chromosomal breaks (Kenton et al, 1993;Kitamura et al, 1997;Chase et al, 2003;Lim et al, 2004;Leitch et al, 2008).…”
mentioning
confidence: 96%
“…The first attempts, carried out by Pearse et al (2006), to synthesize Na and No allopoylploids were unsuccessful, thus the authors used Nicotiana miersii as a maternal surrogate for No (the species most phylogenetically related to No) to create the synthetic neoallopolyploid, Nicotiana 3 mierata. By eliciting plants with OS and methyl jasmonate (MeJA) and comparing the changes in TPI activity, secondary metabolites, and released volatile organic compounds in the parents with those of the neoallopolyploid lines, the authors concluded that parental signaling cascades eliciting these defense responses had been reshuffled in the neopolyploids in a plug-and-play fashion to allow different secondary metabolite responses to be elicited by the diversity of OS-and JA-elicited signaling systems found in the parents.…”
mentioning
confidence: 99%
“…For example, Coate et al (6) showed that tolerance to chronic light stress was significantly increased in a newly formed allotetraploid of soybean (Glycine dolichocarpa) compared with its diploid progenitors. Neoallopolyploid tobacco (Nicotiana miersii × Nicotiana attenuata) showed an innovation of defense against herbivores (7). Both natural and artificial Arabidopsis tetraploids exhibit higher potassium uptake and salinity tolerance than their diploid counterparts (8).…”
mentioning
confidence: 99%